Analisis Penerapan Pembelajaran Berdiferensiasi dalam Implementasi Kurikulum Merdeka pada Mata Pelajaran Matematika Bangun Ruang Siswa Sekolah Dasar (Studi Kasus di Kelas 4 SDN Cakung Barat 01 Jakarta Timur) - Diah Sartika Sari; Kowiyah Kowiyah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Differentiated learning in the independent curriculum provides learning opportunities for students with different backgrounds, including economics, abilities, and characteristics In the mathematics subject of building space, real concepts are used in accordance with the differentiated approach. However, differentiated learning in the implementation of the independent curriculum is still limited. Researchers conducted research using qualitative methods with a case study approach. However, the implementation is still limited. This research uses a qualitative method with a case study approach in grade 4 of SDN Cakung Barat 01 East Jakarta. The research objectives include: 1) Understand the differentiated learning system in Merdeka curriculum, 2) Knowing the components of the Merdeka curriculum at the school, and 3) Identifying the application of differentiated learning in space building mathematics. Data sources come from books, observations, and interviews. The results showed that differentiated learning includes three main aspects in the implementation of the independent curriculum in the subject of building space math in grade 4, including: 1) A learning system that provides opportunities for students with different levels of ability, with an important role from parents; 2) Components that include content, process, product, and adaptive learning environment; 3) Specific application to the mathematics of building spaces by using surrounding objects as learning tools. Students are also more directed to recognize space with objects that are around the classroom and school.